Social Computing, Behavioral-Cultural Modeling and Prediction 4th International Conference, SBP 2011, College Park, MD, USA, March 29-31, 2011. Proceedings - Salerno, John.; Yang, Shanchieh Jay.; Nau, Dana.; Chai, Sun-Ki.; SpringerLink (Online service). (Berlin, Heidelberg Springer Berlin Heidelberg, 2011)
This book constitutes the refereed proceedings of the 4th International Conference on Social Computing, Behavioral-Cultural Modeling and Prediction, held in College Park, MD, USA, March 29-31, 2011. The 48 papers and 3 keynotes presented in this volume were carefully reviewed and selected from 88 submissions. The papers cover a wide range of topics including social network analysis; modeling; machine learning and data mining; social behaviors; public health; cultural aspects; and effects and search.
Electronic reproduction.
Keywords: Online social networks -- Psychological aspects -- Congresses; Interpersonal relations -- Congresses; Interactive computer systems -- Congresses; Electronic books